A STUDY TO ASSESS THE FACTORS INFLUENCING UNMET NEED OF FAMILY PLANNING AMONG MARRIED WOMEN IN SELECTED VILLAGES OF UDUPI DISTRICT, KARNATAKA - R., Lekshmi A.; Ansuya; Manjula (Journal of Health and Allied Sciences NU, 2014)
Background: Millions of women worldwide who are sexually active, who would prefer to avoid becoming pregnant, but are not using any contraception, these women are considered to have an “unmet need” for Family Planning. The concept of “unmet need” points to 1 the gap between some women's reproductive intensions and their contraceptive behaviour. Bridging the gap can lead to a great success in the family planning programme and realization of the dream of stable population.Objectives: To assess the unmet need of family planning and the factors influencing the unmet need among married women.Materials and Methods:A descriptive survey was under taken among 280 married women selected using purposive sampling. Data were collected using structured questionnaire.Results: About 41.1% of the total subjects had the unmet need for family planning in that 32.2% were having unmet need for spacing and 67.8% for limiting. Majority (55.7%) were not using family planning because of fertility related reasons. The study revealed that there was a significant association between unmet need and variables like age and number of living children. There was a significant association between unmet need and fertility related reasons.Conclusion: Since the unmet need of family planning is existing, awareness of the public in relation to family planning should be ongoing especially to the general public with lower level of education.
Keywords: Family planning; factors influencing unmet need